Афанасий Лужанин: улэмез но творчествоез сярысь / [дасяз Д. А. Яшин] - Яшин Даниил Александрович (Удмурт писательёс, 1973)
Экземпляры: кр (20220215) / Инвентарный номер: 51712 / Сис.шифр: 83.3(2Рос=Удм) / Авт.знак: Л 83 / ГРНТИ: 17 / ББК: 83.3(2Рос=Удм)